Which Factors Drive Major Change and University Dropout? An Analysis on International Degree-Seeking Students at German Universities - Thies, Theresa; Falk, Susanne (Journal of International Students, 2023)
Germany is a non-English speaking country with a large and growing number of incoming international degree-seeking students. However, their estimated dropout rates are high. This study aims to investigate whether specific challenges faced by international students (e.g., social and academic integration, language learning, financial situation, residence-permit related regulations) are associated with major change and university dropout. The discrete-time competing risk analyses of the first three semesters of an online panel survey of international students in Germany (International Student Survey; N = 3,660) show that satisfaction with the degree program’s content decreases the risk of major change and university dropout. Moreover, the nationality and the associated temporary or permanent residence permit are considered in the students’ educational decisions. Based on the results, we recommend improving the match between students’ interest and their fields of study. Measures to prevent international students from dropping out must thus begin before they start their studies.